ACID-BASE SURFACE CHEMISTRY AND SORPTION OF SOME LANTHANIDES ON K+-SATURATED, MARBLEHEAD ILLITE: II. A MULTISITE-SURFACE COMPLEXATION MODELING - Kulik D.A.; Sinitsyn V.A.; Aja S.U.; Wood S.A. (My University, 2000)
The surface reactivity and sorption of Nd and Eu onto K+-saturated, Marblehead illite has been investigated in 0.01, 0.1, and 1.0 M KCl solutions at 25°C; the potentiometric titrations were conducted using back-titration techniques. Batch experimental protocols were used in both series of studies. The ionic strength-dependent, proton surface charge density (σH) varies from −1500 to −1700 mC/m2 in 1.0 M KCl solutions and from −1800 to −2200 mC/m2 in 0.01 and 0.1 M KCl solutions. An isoelectric point was not defined by the σH vs. pH curves, which reflects the multi-phase nature of natural illitic materials. The functional dependence of REE binding constants (log Ke) on surface coverage (log ΓREE) indicates the existence of a multiplicity of energetically distinct surface types. These surface site types include amphoteric silanol and aluminol sites, basal planar surfaces, and “frayed edges”; the frayed edges are observed only in low ionic strength solutions (I ≤ 0.1 M KCl).